A two-stage maintenance trial of cetuximab-based treatment in RAS and BRAF wild-type unresectable metastatic colorectal cancer: a retrospective real-world study - Jiang, Tao; Chen, Hao; Wang, Xinli; Lin, Fangyu; Wang, Han; Liu, Jialin; Lin, Xiaoyan (Frontiers in Oncology, 2024)
Background: To investigate the effectiveness and safety of maintenance regimens based on cetuximab, we conducted a real-world, single-arm, retrospective study at a single center. Methods: In Fujian Medical University Union Hospital, patients with unresectable metastatic colorectal cancer (mCRC) who received cetuximab-based maintenance therapy between December 2020 and December 2021 were included. All patients had RAS and BRAF wild-type. The maintenance regimen consisted of 6–12 cycles of cetuximab plus irinotecan (Phase 1) and cetuximab (Phase 2). Patients could receive reintroduction therapy in case of disease progression during Phase 2. Progression-free survival (PFS), overall survival (OS), and safety data were collected. Results: According to the inclusion and exclusion criteria of the study, a total of 108 subjects who received maintenance therapy were included— 51 experienced disease progression during Phase 1, with PFS(1) of 7.3 months. Among the 52 patients who entered Phase 2, 17 were still in this phase at the end of follow-up, with PFS (2) of 10.1 months. In Phase 2, 35 patients experienced disease progression, of whom 24 received reintroduction therapy, with PFS (3) of 6.7 months. The overall PFS (total) during the maintenance period was 11.9 months, and the OS was 39.2 months. Grade III or higher adverse events were 4.6% during Phase 1 and 0% during Phase 2. Conclusion: Innovative cetuximab-based maintenance therapy showed a trend toward improving the prognosis of mCRC patients with RAS and BRAF wild-type, while the toxic side effects of maintenance therapy were manageable.